PENGARUH VARIABEL STRUKTUR AKTIVA, UKURAN PERUSAHAAN, PROFITABILITAS, LIKUIDITAS DAN DEVIDEN PAYOUT RATIO TERHADAP STRUKTUR MODAL - Choiruddin, Muhammad Nanang (Fakultas Ekonomi, UIN Maliki Malang, 2014)
This research is conducted to examine the influence of asset structure variable, size, profitability,liquidity, dividend payout ratio influence capital structure in the consumer goods industry sector companywhich has recorded in Indonesian security exchange (IDX) on 2008–2012 period. This research uses dependentvariable capital structure, independent variable is asset structure, size, profitability, liquidity, devidend payoutratio. The sample is 29 consumer goods industry sector company. The result of F test, the research in consumergoods industry sector company in Indonesia show that all independent variables to capital stucture issignificant. The analysis result of t-test, show that asset structure variable, size, profitability and liquidity tocapital stucture are negative significant. Devidend payout ratio to capital structure is not significant. Thisresult explains that the change of capital structure in the consumer goods industry sector company is notinfluenced by devidend payout ratio. For continued research is suggested used type sample of anothercompany which has not been observed with wider scope of research which has more population with longerperiod and should give additional of the number of variable which influence capital structure.